Blood Pressure Changes Following Aerobic Exercise in Caucasian and Chinese Descendants - Sun, P.; Yan, H.; Ranadive, S. M.; Lane, A. D.; Kappus, R. M.; Bunsawat, K.; Baynard, T.; Li, S.; Fernhall, B. (International Journal of Sports Medicine, 2015)
Acute aerobic exercise produces post-exercise hypotension (PEH). Chinese populations have lower prevalence of cardiovascular disease compared to Caucasians. PEH may be associated cardiovascular disease through its influence on hypertension. The purpose of this study was to compare PEH between Caucasian and Chinese subjects following acute aerobic exercise. 62 (30 Caucasian and 32 Chinese, 50% male) subjects underwent measurement of peripheral and central hemodynamics as well as arterial and cardiac evaluations, 30 min and 60 min after 45 min of treadmill exercise. Caucasians exhibited significantly higher baseline BP than the Chinese. While the reduction in brachial artery systolic BP was greater in Caucasian than in the Chinese, there was no difference in changes in carotid systolic BP between the groups. The increase in cardiac output and heart rate was greater in the Chinese than Caucasians, but total peripheral resistance and leg pulse wave velocity decreased by a similar magnitude in the Chinese and Caucasian subjects. We conclude that acute aerobic exercise produces a greater magnitude of PEH in peripheral systolic BP in Caucasian compared to Chinese subjects. The different magnitude in PEH was caused by the greater increase in cardiac output mediated by heart rate, with no change in stroke volume. It is possible that initial BP differences between races influenced the findings.
Keywords: post exercise hypotension; cardiac output; total peripheral resistance; racial differences